A tribute to Dr. Saul Hertz: The discovery of the medical uses of radioiodine - Hertz, Barbara (World Journal of Nuclear Medicine, 2019)
Dr. Saul Hertz was Director of The Massachusetts General Hospital's Thyroid Unit, when he heard about the development of artificial radioactivity. He conceived and brought from bench to bedside the successful use of radioiodine (RAI) to diagnose and treat thyroid diseases. Thus was born the science of theragnostics used today for neuroendorine tumors and prostate cancer. Dr. Hertz's work set the foundation of targeted precision medicine.
Keywords: Dr. Saul Hertz; nuclear medicine; radioiodine